Indian Economy - Datt,Gaurav & Nag,Biswajit (UP S.Chand, 2024)
The revised edition of Datt and Sundharam's "Indian Economy" provides a contemporary and comprehensive review of India's economic development. This edition, aligned with the National Education Policy 2020, reflects a critical understanding of the dynamic challenges and opportunities facing the country. Divided into five parts, it covers the evolving structure, planning system, societal concerns, fiscal policies, and global aspects of the Indian economy. Packed with data presented through tables, graphs, and charts, the book is informative and visually appealing. Tailored for undergraduate Economics students, it also serves postgraduates, researchers, and competitive exam aspirants, offering insights into the potential and limits of economic policy in India.
Keywords: Economy Sector; Indian economic development